Os topónimos algarvios na Paleontologia portuguesa - Rocha, R. B. (2011)
Since the XIX century, Portuguese and foreign geologists have defined 47 new invertebrate taxa (foraminifera, ostracods, coelenterates, brachiopods, gastropods, ammonoids, echinoids), 2 new fossil plant taxa (charophyte and pteridophyte) and 1 ichnofossil, using toponymy from the Algarve; these taxa refer to 1 genera, 47 species and 2 varieties. Besides the Algarve toponym, the most used as specific name, twenty others have been used, mostly from western Algarve; these toponyms are associated to: – Miocene units, particularly from Ribeira de Cacela and Ferragudo; – Cretaceous units between Zavial and Marim; – Upper Jurassic units from Sagres, Carrapateira and Loulé and Middle Jurassic units from Sagres and Guilhim; – Triassic units from Vila do Bispo to Tavira; – Carboniferous units, particularly from the Aljezur-Bordeira-Carrapateira region. The earliest of these designations were attributed to seven gastropods from the Upper Miocene of Cacela (COSTA, 1866-1867). The majority of the named species are typical of the Algarve, but some have been collected, as well, in the Lusitanian Basin. Although extensively cited in the geological literature, some of these taxa either do not fulfill the ICZN rules, or fall into synonymy with previously established taxa, or should be formally considered as non valid names (nomem nudum and nomen oblitum). Only widespread bibliographical review, associated with the palaeontological revision of some of these groups and the correct interpretation of the ICZN articles, will allow confirming, or not, the doubts that have now arisen.